Climate Change Impacts on Animal Husbandry in Africa : A Ricardian Analysis - Seo, Sungno Niggol (World Bank, Washington, DC, 2012)
This paper analyzes the impact of climate change on animal husbandry in Africa. It regresses the net revenue from raising animals in small and large farms across Africa on climate, soil, and other control variables to test the climate sensitivity of livestock. The study is based on a survey of over 9,000 farmers across 11 countries conducted by the World Bank and the Global Environment Facility. From this dataset, 5,400 farms were found to rely on livestock. The paper develops models to test whether the climate coefficients of small and large farms are similar. It turns out that small farms tend to be more labor intensive, rely on native stocks, and have few animals. Large farms tend to be more commercial operations, with much larger stocks and more modern approaches. The analysis finds that warming is good for small farms because they can substitute animals that are heat tolerant. Large farms, by contrast, are more dependent on cattle, which are not heat tolerant. The wetter scenarios are likely to be harmful to grazing animals because greater rainfall implies a shift from grasslands to forests, an increase in harmful disease vectors, and a shift from livestock to crops. Overall, because large farms dominate the sector, African livestock net revenues are expected to fall. However, if future climates turn out to be dry, livestock net revenue will increase. At least against the risk of dryness, livestock offer a good substitute for crops.